(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Mercury (Hg) is a heavy metal with high toxicity and poses a significant threat to living organisms. This article discusses the harmful effects of mercury on human and animal health, its routes of exposure, bioaccumulation processes, and cellular toxicity mechanisms. Mercury severely affects the central nervous system, kidneys, and immune system. Methylmercury, in particular, is the most toxic form, entering the human body through the food chain. Studies have shown that mercury disrupts enzymatic systems, increases oxidative stress, and damages genetic material. This article highlights the importance of preventing mercury poisoning and ensuring environmental safety.